2019
DOI: 10.1096/fj.201802659rr
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin ameliorates experimental colitis by modulating microbiota composition and T reg /T h 17 balance

Abstract: Inflammatory bowel diseases (IBDs) are characterized by chronic pathologies associated with extensive gut dysbiosis and intestinal inflammation. Hence, endeavors to improve the inflammatory pathology by manipulating gut microbiota are ongoing. Daphnetin (DAPH) is a coumarin derivative extracted from Daphne odora var with anti‐inflammatory and immune‐regulatory properties that has been widely used in treating inflammatory disorders. Herein, we showed that DAPH remarkably alleviated experimental colitis by reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…Hyperuricemic mice received gut microbiota via transplants from the control, model, or TMOP groups to further substantiate whether the beneficial effects of TMOP were mediated by gut microbiota. FMT-LD-TMOP alleviated hyperuricemia and renal inflammation phenotypes, consistent with other studies on obesity, colitis, etc,, 30,41 and the beneficial effects were characterized by the reversal in uric acid metabolism and pro-inflammatory cytokine release, and inhibition of the NLRP3 inflammasome and TLR4/NF-κB signaling pathways activations (Figure 7). Meanwhile, FMT-LD-TMOP mice exhibited repaired gut intestinal integrity and increased SCFA productions, similar as the corresponding diet-treated mice (LD-TMOP group) ( Figure 8A-F).…”
Section: Discussionsupporting
confidence: 89%
“…Hyperuricemic mice received gut microbiota via transplants from the control, model, or TMOP groups to further substantiate whether the beneficial effects of TMOP were mediated by gut microbiota. FMT-LD-TMOP alleviated hyperuricemia and renal inflammation phenotypes, consistent with other studies on obesity, colitis, etc,, 30,41 and the beneficial effects were characterized by the reversal in uric acid metabolism and pro-inflammatory cytokine release, and inhibition of the NLRP3 inflammasome and TLR4/NF-κB signaling pathways activations (Figure 7). Meanwhile, FMT-LD-TMOP mice exhibited repaired gut intestinal integrity and increased SCFA productions, similar as the corresponding diet-treated mice (LD-TMOP group) ( Figure 8A-F).…”
Section: Discussionsupporting
confidence: 89%
“…Maduzia et al., (2020) [ 51 ], in their study also showed a similar protective effect exhibited by warfarin treatment before the induction of acute pancreatitis in the model employed in the study. Anti-inflammatory, protective and therapeutic effects have been observed in other studies on colons on the administration of coumarins such as daphnetin [ 52 ], 4-methylesculin [ 53 ], or osthole [ 54 ]. Although studies have not been done on the anticoagulant effect of bergapten, results from these experiments conducted indicate that possible, anti-inflammatory action shown by bergapten may be due to its possible anticoagulant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liu et al (26) reported that DAP has protective effects on severe acute pancreatitis in a rat model by inhibiting the expression of inflammatory cytokines. Ji et al (32) demonstrated that DAP ameliorates experimental colitis by modulating microbiota composition and the Treg/Th17 balance. Currently, an increasing number of studies have demonstrated that DAP serves a crucial role in the prevention and treatment of inflammation-related diseases due to its powerful anti-inflammatory activities (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (26) reported that DAP has some protective effects on severe acute pancreatitis in a rat model by inhibiting the expression of inflammatory cytokines. Subsequently, DAP was found to prevent and treat numerous diseases, including cerebral ischaemia/reperfusion injury, rheumatoid arthritis, colitis and endotoxin-induced lung injury, due to its powerful anti-inflammatory activities (24,(27)(28)(29)(30)(31)(32). At present, DAP is an anti-inflammatory agent used in some inflammation-related diseases (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%